Developing Social Empathy Character Through Contextual Leraning of Zakat and Sadaqah Material at MIN 1 Bantul - Tsaaniyatush Shoolihah Fauzan (Konsultan Jurnal Ilmiah Indonesia, 2025)
This qualitative research aims to explore the development of social empathy character through contextual learning of zakat and sadaqah material at MIN 1 Bantul. Using a descriptive qualitative approach with case study method, data were collected through in-depth interviews, participant observation, and documentation. The research subjects consisted of Islamic Religious Education (PAI) teachers, students, and school principals. The results showed that contextual learning of zakat and sadaqah effectively develops students' social empathy through three main strategies: (1) direct observation of social conditions in the surrounding environment, (2) zakat and sadaqah practice projects involving students directly, and (3) reflection and discussion on the social impacts of zakat and sadaqah. The findings indicate that when zakat and sadaqah materials are taught contextually by connecting them to real social realities, students not only understand the concepts theoretically but also develop sensitivity and empathy towards others' social conditions. This research contributes to the development of character-based PAI learning methods in elementary madrasahs.